2017
DOI: 10.1152/physiolgenomics.00081.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic aerobic capacity governs the associations between gut microbiota composition and fat metabolism age-dependently in rat siblings

Abstract: Host genetic factors affecting the gut microbiome play an important role in obesity, yet limited attention has been paid on the host genetic factors linked to physical fitness in modifying the microbiome. This study determined whether sibling-matched pairs of rats selectively bred for high (HCR) and low (LCR) aerobic capacity differ in their microbiome age-dependently and which taxa associate with differential in metabolism. Several taxa in young adult rats (hereafter young) linked to inherited aerobic capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
2
10
0
2
Order By: Relevance
“…The major findings of this study indicate that the six-weeks guided endurance exercise training induced modest shifts in gut microbiota both at taxonomical and functional level. In accordance, animal studies by us and others have reported that high-intensity endurance training modified the gut microbiota (Campbell et al, 2016 ; Denou et al, 2016 ) and, that intrinsic aerobic capacity impacts the microbiota composition (Pekkala et al, 2017 ). In recent times, accumulating attention has been addressed to the possible link between gut microbiota and physical fitness also in humans.…”
Section: Discussionsupporting
confidence: 80%
“…The major findings of this study indicate that the six-weeks guided endurance exercise training induced modest shifts in gut microbiota both at taxonomical and functional level. In accordance, animal studies by us and others have reported that high-intensity endurance training modified the gut microbiota (Campbell et al, 2016 ; Denou et al, 2016 ) and, that intrinsic aerobic capacity impacts the microbiota composition (Pekkala et al, 2017 ). In recent times, accumulating attention has been addressed to the possible link between gut microbiota and physical fitness also in humans.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, Firmicutes , Bifidobacterium , and Lactobacillus have multiple beneficial effects on host metabolism, producing energy and short-chain fatty acids (SCFAs) (Antunes et al 2019 ; Bang et al 2018 ; Blakeley-Ruiz et al 2019 ). Furthermore, the intestinal microbiota regulates carbohydrate and lipid metabolism (Li et al 2018a , b ; Pekkala et al 2017 ), providing the host with sources of energy or activating receptors (Federici 2019 ). Intestinal microorganisms are also involved in the synthesis of key vitamins that cannot be produced by their host organisms (Grieneisen et al 2019 ; Martin et al 2018 ; Srugo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is widely known that gut microorganisms are indispensable for the host nutrient absorption and metabolism (De Mandal et al 2018;Deng et al 2019;Dong et al 2018;Pan et al 2019;Si et al 2020), for instance, Firmicutes, Bi dobacterium, and Lactobacillus, which have multiple bene cial effects on host metabolism to produce energy and short-chain fatty acids (SCFAs) (Antunes et al 2019;Bang et al 2018;Blakeley-Ruiz et al 2019). Furthermore, the intestinal microbiota regulates carbohydrate and lipid metabolism (Li et al 2018b;Pekkala et al 2017), provide the host with source of energy or activate receptors (Federici 2019). It is worth mentioning that intestinal microorganisms are involved in the synthesis of key vitamins that cannot be produced by the host organisms (Grieneisen et al 2019;Martin et al 2018;Srugo et al 2019).…”
Section: Introductionmentioning
confidence: 99%